High dose right unilateral versus moderate dose bilateral ECT for major depression : time to re-orientation, physical functioning, quality of life and attitudes - Kavanagh, Adam (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2012)
The objective of this study was to compare the effects of 1.5 x seizure threshold (ST) bitemporal ECT with high dose (6 x ST) right unilateral (RUL) ECT with respect to immediate recovery from treatment, change in physical functioning and health related quality of life (HRQOL) and the attitudes of service users towards these different treatments with 6 months follow-up. 100 participants were randomly allocated to receive 1.5 x ST bitemporal ECT or high dose (6 x ST) RUL ECT, N = 50 per group. ECT was administered twice weekly. Participants were administered a battery of clinical and neurocognitive assessments prior to treatment, at the end of treatment course, 3 months and 6 months after the end of treatment. This study provides a unique opportunity to obtain prospective data on high-dose RUL ECT and compare this to the standard version. Recovery data were used to compare time to reorientation and the incidence of physical side effects immediately following treatment between groups. The Physical Self Maintenance Scale and Instrumental Activities of Daily living Scale were used to compare the different forms of ECT regarding their effect on physical functioning in severe depression. The Medical Outcomes Study Short Fonn 36 Item Health Survey was used to compare the effects of the different forms of ECT on HRQOL over time. Attitudes of service users towards the different forms of ECT were explored for the first time using a combination of two published ECT attitudes questionnaires. Using a Cox Mixed Effects survival model high dose RUL ECT was associated with quicker reorientation after treatment of approximately 65% for the first treatment session and 44% for subsequent treatment sessions. There was no difference between the treatment groups in the number of participants that experienced prolonged disorientation.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin